ORIGINAL PAPER The influence of weather on articular complaints of patients with osteoarthritis - Janus, Danuta; Drabiszczak, Janina; Zakrzewska, Aleksandra (Reumatologia/Rheumatology, 2005)
The aim of the present work was to study the correlation between meteorological parameters (temperature, air humidity, atmospheric pressure) and complaints of patients suffering from osteoarthritis (OA); gonarthrosis and/or coxarthrosis. The investigation comprised 50 outpatients from Warsaw and its suburbs. Baseline examination included: physical examination and that of the locomotor system and basic laboratory tests. Then, every evening for a fortnight, patients filled questionnaire, estimating pain intensity, stiffness of joints and degree of difficulties in performing everyday activities. Patients’ complaints were correlated with the data obtained from Meteorology Institute. The results obtained in static and dynamic conditions were analyzed. OA patients experienced greater joint pains when air temperature was lower. Pains of joints and difficulties in performing everyday activities increased when the changes of temperature, humidity and atmospheric pressure were greater. The stiffness of joints elongated during greater changes of temperature and humidity and during constant atmospheric pressure. The inter-relations observed can help to foresee periods of intensified complaints from OA patients, and, consequently, to use preventive measures.